PENGARUH KOMITE AUDIT DAN FEE AUDIT TERHADAP KUALITAS AUDIT PADA PERUSAHAAN BUMN DI INDONESIA - Pedi Riswandi; Rina Yuniarti; Subandrio Subandrio (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2024)
This study aims to analyze and determine the effect of good corporate governance and audit fees on audit quality in state-owned companies listed on the Indonesia Stock Exchange in 2018-2023. This type of research is quantitative research. The sampling technique uses purposive sampling techniques with a total research sample of 75 companies. This research uses secondary data obtained through the company's annual report and financial statements during the 2018-2023 period. The analysis technique used is logistic regression analysis. The results of the study using SPSS version 25 showed that: (1) Audit committee has a negative and insignificant effect on audit quality, (2) Audit fees have a positive and significant effect on quality. Keywords: Institutional Ownership, Audit Committee, Audit Fee, Audit Quality.